EQUITABLE ACCESS TO HEALTH SERVICE IN BANYUWANGI - Lusi Herawati Sunyoto Usman Mark Zuidgeest (Universitas Gadjah Mada, 2012)
Equitable health care is a basic right for citizens and must be fulfilled by the government. This research analyzed communitydiscrepancy in access to reach health services in public hospitals and Puskesmas (health centers) in Banyuwangi Regency.This research identified community accessibility to health facilities services using travel time and transport modes choiceas indicators. Flowmap tool is used to analyze catchment area of each health facility using different transport modes choice:becak and public transport for poor group and motorcycle and car for non-poor group with different travel time within 30, 60 and more than 60 minutes. It is concluded that there was an accessibility difference between poor and non-poor group. The accessibility to the health facilities of poor group was lower than non-poor group. This condition occurred because the government policy of equitable access to health service facility did not pay attention to accessibility of poor group.